Antenatal screening of syphilis: diagnosed by rapid plasma regain and rapid immunochromatography method - Dr. Nidhi Barot; Dr. Hetvi Chawda; Megha Patel (Tropical Journal of Pathology and Microbiology, 2019)
Background: Syphilis is one of the major causes of adverse outcomes in pregnancy in developing countries. Antenatal screening for syphilis aims primarily at timely detecting & treating pregnant women with congenitally transmissible syphilis, there by preventing perinatal deaths. Objective: To study prevalence of syphilis in antenatal women by screening them with the Rapid Plasma Reagin (RPR) & rapid immunochromatographic (ICT) method. Materials and Methods: A total of 2258 pregnant women attending antenatal care from January to December 2018 were tested for Syphilis by RPR & rapid ICT. Results: Out of 2258 women screened during their antenatal visits, 12 (0.53%) were positive by RPR as well as rapid ICT test method. Conclusion(s): Early detection of syphilis in pregnancy is the best tool for prevention of adverse pregnancy outcomes. Antenatal screening of syphilis with Rapid plasma regain (RPR) and Rapid immunochromatography (ICT) is sensitive, specific, rapid and cost-effective method.